2015
DOI: 10.1186/s12911-015-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of electronic patient-reported outcome assessment with cancer patients in the hospital and at home

Abstract: BackgroundPatient-reported outcomes (PRO) provide a more comprehensive picture of patients’ quality of life than do mere physicians’ ratings. Electronic data collection of PRO offers several advantages and allows assessments at patients’ homes as well. This study reports on patients’ personal internet use, their attitudes towards electronic and web-based PRO assessment (clinic-ePRO and home-ePRO) and the feasibility of these two assessment modes.MethodsAt the Medical University of Innsbruck and Kufstein County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 22 publications
6
63
0
3
Order By: Relevance
“…B. [35,36]), ohne die vielfältigen die Nutzenbereitschaft beeinflussenden Faktoren (bezogen z. B. auf die HRQoL, die krankheits-oder therapiebezogenen Belastungen, soziodemografische Faktoren, Technikvorerfahrungen oder die Bereitschaft zur Nutzung) zu berücksichtigen [31,32].…”
Section: Wissensstand Zu Praktikabilität Und Leistungsfähigkeitunclassified
See 1 more Smart Citation
“…B. [35,36]), ohne die vielfältigen die Nutzenbereitschaft beeinflussenden Faktoren (bezogen z. B. auf die HRQoL, die krankheits-oder therapiebezogenen Belastungen, soziodemografische Faktoren, Technikvorerfahrungen oder die Bereitschaft zur Nutzung) zu berücksichtigen [31,32].…”
Section: Wissensstand Zu Praktikabilität Und Leistungsfähigkeitunclassified
“…Auch die technischen Herausforderungen sind bisher kaum erforscht, da in vielen Studien lediglich selbstentwickelte ePRO-Instrumente erprobt und evaluiert werden (z. B [36]…”
unclassified
“…PALM: In the Blum et al (2014) study, 49% of the 84 participants preferred the PALM (handheld computer) to the paper-based assessment. Several studies reported high patient acceptability and feasibility regarding the electronic assessment of symptoms (Abernethy et al, 2008;Andikyan et al, 2012;Basch et al, 2007;Blum et al, 2014;Chan et al, 2011;Falchook et al, 2016;Wintner et al, 2015;Wolpin et al, 2008;Wu et al, 2016). Three studies (Head et al, 2009;Mirkovic, Kaufman, & Ruland, 2014;Ruland, Maffei, et al, 2013) considered the usability and usefulness of a device from the patient's perspective.…”
Section: Touchscreen Computerized Survey Assessing Psychosocial Well-mentioning
confidence: 99%
“…B. 35,36], ohne die viel fältigen die Nutzenbereitschaft beeinflussenden Faktoren (bezo gen z. B. auf die HRQoL, die krankheits oder therapiebezogenen Belastungen, soziodemografische Faktoren, Technikvorerfahrun gen, oder die Bereitschaft zur Nutzung) zu berücksichtigen [31,32].…”
Section: Wissenstand Zu Praktikabilität Und Leistungsfähigkeitunclassified